Redescriptions of two poorly known species of Zodariellum Andreeva & Tystshenko, 1968 (Araneae, Zodariidae) from Uzbekistan - Esyunin Sergei L.; Zamani Alireza; Marusik Yuri M. (Tarbiat Modares University Press, 2025)
Two poorly known species of the zodariid spider genus Zodariellum Andreeva & Tystshenko, 1968 – Z. spasskyi (Charitonov, 1946) and Z. zebra (Charitonov, 1946) – are redescribed based on type specimens from eastern Uzbekistan. Additionally, a lectotype is designated for the former species.